Increasing the Biostability of Concrete by the Introduction Of Additives - Rumyantseva Varvara; Konovalova Viktoriya; Narmaniya Boris; Korinchuk Mikhail (E3S Web of Conferences, 2023)
To increase the resistance to fungal corrosion and improve the performance of concrete cement stone, it is proposed to introduce calcium stearate and active metal nitrates in an amount of 0.5% by weight of cement into the cement mixture at the manufacturing stage. To determine the degree of corrosion damage of cement stone by fungal microorganisms Aspergillus niger, porosity, density, water absorption and strength were determined. It has been found that the introduction of a hydrophobic additive of calcium stearate into the cement mixture during the manufacture of concrete reduces water absorption, reduces porosity and increases strength. Additives of nitrates of active metals do not affect the characteristics of the cement stone of concrete. As a result of 6 months of fungal corrosion, the water absorption, porosity and density of cement stone containing calcium stearate did not change, and the strength decreased by 4%. Metal nitrates do not prevent damage to the cement stone by microorganisms, but slow down the flow of aggressive substances to the surface of the reinforcement in concrete. The combined introduction of calcium stearate and nitrates into the cement mixture will improve the characteristics of concrete, increase its corrosion resistance and ensure the safety of reinforcement in concrete.